Agent‐Based Modeling of Alternative Futures in the British Land Use System. Issue 11 (2nd November 2022) - Brown, C.; Seo, B.; Alexander, P; Burton, V.; Chacón‐Montalván, E. A.; Dunford, R.; Merkle, M.; Harrison, P. A.; Prestele, R.; Robinson, E. L.; Rounsevell, M.
Abstract: Socio‐economic scenarios such as the Shared Socioeconomic Pathways (SSPs) have been widely used to analyze global change impacts, but representing their diversity is a challenge for the analytical tools applied to them. Taking Great Britain as an example, we represent a set of stakeholder‐elaborated UK‐SSP scenarios, linked to climate change scenarios (Representative Concentration Pathways), in a globally‐embedded agent‐based modeling framework. We find that distinct model components are required to account for divergent behavioral, social and societal conditions in the SSPs, and that these have dramatic impacts on land system outcomes. From strong social networks and environmental sustainability in SSP1 to land consolidation and technological intensification in SSP5, scenario‐specific model designs vary widely from one another and from present‐day conditions. Changes in social and human capitals reflecting social cohesion, equality, health and education can generate impacts larger than those of technological and economic change, and comparable to those of modeled climate change. We develop an open‐access, transferrable model framework and provide UK‐SSP projections to 2080 at 1 km 2 resolution, revealing large differences in land management intensities, provision of a range of ecosystem services, and the knowledge and motivations underlying land manager decision‐making. These differences suggest the existence of large but underappreciated areas of scenario space, within which novel options for land system sustainability could occur. Key Points: A national‐scale agent‐based model is developed to represent paired climatic and socio‐economic scenarios in the land system Key scenario characteristics relate to forms of human behavior, interactions and societal preferences Large differences emerge between scenarios in terms of land management intensities, ecosystem service provision and land sparing